To Love and Be Loved - Benjamin Y. Fong (The European Journal of Psychoanalysis, 2022)
In “Instincts and their Vicissitudes,” Sigmund Freud entertains the possibility of a third developmental stage beyond the oppositions love-indifference and love-hate: love-being loved. Though he casually dismisses the possibility in the paper itself, the polarity love-being loved demands investigation, as it seems to signal a higher form of sublimation than we typically find in Freud’s writings.
Keywords: Freud; love; Hate; Indifference; instincts